The Impact of Financial Technology on Bank Financial Performance - Efris Saputri, Eka Julianti; Pradana, Aditya; Apriandi, Rian Fitra; Taufik, Haviz (TIN: Terapan Informatika Nusantara, 2024)
This research was conducted to determine whether there is a significant influence on financial performance before and after the operation of Financial Technology (Fintech) in Jambi. The variables used in this study employed financial ratios, namely Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return Of Assets (ROA), Operational Efficiency Ratio (BOPO), and Non-Performing Loan (NPL) in banks registered with the Financial Services Authority (OJK) for the period 2015-2018. The testing methods utilized in this research include the Paired Sample T-test for normally distributed data and the Wilcoxon Sign Rank Test for non-normally distributed data. The findings of this study indicate a significant influence on the financial ratios of CAR and BOPO. Meanwhile, for the variables ROA, LDR, and NPL, there is no significant influence on the financial performance of banking companies before and after the emergence of Financial Technology (Fintech) in Jambi.